Performance optimization strategies of halide perovskite-based mechanical energy harvesters - Jiang, Feng (2022)
Halide perovskites, possessing unique electronic and photovoltaic properties, have been intensively investigated over the past decade. The excellent polarization, piezoelectricity, dielectricity and photoelectricity of halide perovskites provide new opportunities for the applications of mechanical energy harvesting. Although various studies have been conducted to develop halide perovskite-based triboelectric and piezoelectric nanogenerators, strategies for their electrical performance optimization are rarely mentioned. In this review, we systematically introduce the recent research progress of halide perovskite-based mechanical energy harvesters and summarize the different optimization strategies for improving both the piezoelectric and triboelectric output of the devices, bringing some inspiration to guide future material and structure design for halide perovskite-based energy devices. A summary of the current challenges and future perspectives is also presented, offering some possible directions for development in this emerging field.